Poly[hemi(ethylenediammonium) [di-μ-oxalato-indium(III)] dihydrate] - Sun, Qiaozhen (International Union of Crystallography, 2009)
In title compound, {(C(2)H(10)N(2))(0.5)[In(C(2)O(4))(2)]·2H(2)O}(n), the unique In(III) ion is coordinated by eight O atoms from four oxalate ligands in a distorted square-antiprismatic environment. The doubly bis-chelating oxalate ligands act as bridging ligands connecting symmetry-related In(III) ions and forming a three-dimensional open framework structure. Ethylenediammonium cations and water molecules occupy the voids within the structure. The unique ethylenediammonium cation and one water molecule both lie on a twofold rotation axis. One of the other two water molecules residing on general crystallographic sites was refined as disordered with half occupancy. In the crystal structure, cations and water molecules are linked to the anionic framework via intermolecular O—H⋯O and N—H⋯O hydrogen bonds.